Prazer, sofrimento e retaliação: um estudo com jovens trabalhadores de Belo Horizonte (MG) - Thaís Pinto da Rocha Torres (2020)
The research of this dissertation aimed to analyze the influence of pleasure and suffering on retaliatory attitudes and effective retaliation of young workers assisted by the Association of Professional Social Teaching (ESPRO) of Belo Horizonte (MG). To this end, a descriptive-explanatory research and quantitative and qualitative approaches were conducted in the case study model. Data were collected through 323 questionnaires and 21 semi-structured interviews, proceeding to univariate and multivariate statistical analysis and content analysis, respectively. The general objective of the study is answered by corroborating that aspects related to suffering may lead to retaliatory attitudes and retaliation; In addition, the increase in professional achievement, a factor linked to pleasure, leads to a decrease in retaliation. The qualitative part of the research evidenced more pleasure than suffering in the work of the approached young people. Among the following theoretical and conceptual contributions, the following stand out: the proposition of an integrated analysis model not found in the Management literature; the study of retaliation, which is a little explored construct in the area, known for privileging positive managerial aspects; the study of the construct pleasure and suffering at work, as well as some changes in the configuration of the ITRA scale factors, probably due to the differentiated public approached; and the integrated study of the constructs, proving the relationship between them through SEM, based on the specificities of young workers to elucidate the new insights. The pragmatic and organizational contribution presents conclusions for organizations to pay attention to the well-being of young people at work, minimizing aspects of suffering revealed in the research that can lead to counterproductive retaliation behaviors, extremely harmful in terms of costs and productivity. Considering the critical results related to physical and cognitive costs, it is up to organizations to seek alternatives to reduce them, as their intensification can cause illness. On the other hand, young people can reflect on the sources of suffering and already create defensive strategies to make work rewarding and pleasurable. Given the limitations of the study, a research agenda was suggested, highlighting the need for further studies that address young workers, as these are the professionals of the future.